3D Animation: Cultivation and Processing of Aren Juice Content in North Sulawesi - Nancy Jeane Tuturoong; Jimmy Reagen Robot (International Journal of Scientific Multidisciplinary Research, 2024)
Aren trees are able to produce raw materials for the craft industry. Almost all parts of the date palm can be used or have a sale value. Aren cultivation is still rarely done due to a lack of attention to the development of Aren plants by various parties. This study aims to make an animated film introducing Aren cultivation which can introduce the process of Aren cultivation. Animations are made in Blender 3D, which is software for creating 3D objects and animations. The method of making animation consist of making storyboards, modelling and texturing, rigging, forming sets, animation and rendering, as well as editing and final rendering. The resulting 3d animation of cultivating Aren is loaded sequentially in the animation starting from geo-content of aren areas, cultivation and processing of the Aren juice until it is ready to be packaged